Putting sustainable human resource management and workplace eudaimonic well-being into cross-cultural context - Wojtczuk‐Turek, Agnieszka; Turek, Dariusz; Jurek, Paweł; Edgar, Fiona; Okay-Somerville, Belgin; Podgorodnichenko, Nataliya; Fu, Na; Järlström, Maria; Popov, Boris; Hutchings, Paul; Sullivan, Katie; Hafstad, Marius Duhović; et al. (Elsevier, 2026)
This study examines how sustainable human resource management (HRM) impacts employee work engagement and eudaimonic well-being across cultural contexts that differ on individualism-collectivism dimension. Theoretically, the study draws from Self-Determination Theory (SDT; Ryan & Deci, 2017) and the model of culture fit (Aycan et al., 1999). Using data from 14,502 employees nested in 54 countries working in a variety of positions across different sectors, we found support for our hypothesized model—that is, sustainable HRM was positively related to employee eudaimonic well-being via enhanced work engagement. The study found that one moderating effect—the relationship between work engagement and eudaimonic well-being—was stronger in countries that are more individualistic rather than collectivistic. The findings provide support for the universality of the SDT-based approach to understanding employee experiences based on sustainable HRM and cultural variations that inform work-related eudaimonic well-being. Our study advances existing cross-cultural research on sustainable HRM and employee well-being.
Keywords: Sustainable HRM; Individualism-collectivism; Eudaimonic well-being; Work engagement; Self determination theory; Model of culture fit; fi=Henkilöstöjohtaminen|en=Human Resource Management|